Propagation of Ammi visnaga (L.) Under the Influence of Inorganic of Some Chromium Metabolites Khellin, Visnaginby in Vitro Culture Technique - Nadhim Salim Ghanim; Ekhlas Meteab Ahmed; Wijdan Saadi Aziz (مجلة ديالى للعلوم الزراعية)
The experiment was carried out. To know the effect of adding KNO3, KH2PO4, and CaCl2 to the callus of the plant Ammi visnaga that produces metabolic compounds khellin and visnagin. The seeds were planted on Woody plant medium (WPM) supplemented with 2,4-Dichlorophenoxyacetic acid at levels 0, 1.5, 2.0, 2.5 and 3.0 mg L-1 mixed with Kinetin 6-furfurylo- amino-purine a level of 2.5 mg L-1. After germination of the seeds the shoot tips were taken and grown on WPM medium supplemented with 2,4-D at 0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 and 5.5 mg L-1 mixed with kinetin at a level. 2.5 mg L-1. After obtaining the callus, it was grown on WPM medium supplied with KNO3 at a level of 0.0, 0.20, 0.30 and 0.40 g L-1 and KH2PO4 at a level of 0.0, 0.20, 0.25 and 0.30 g L-1 and CaCl2.2H2O at a level of 0.0, 0.20, 0.30 and 0.40 g L-1.The results showed that the level was 3.0 mg L-1 of 2,4-D and Kinetin at 2.5 mg L-1 gave the highest germination rate. The level of 3.0 mg L-1 2,4-D with 2.5 mg L-1 Kinetin achieved the highest percentage of callus formation 95.80%. The highest level of visnagin and khellin was obtained when adding KNO3 at a level of 0.30 g L-1, KH2PO4 at a level of 0.30 g L-1 and CaCl2 at a level of 0.20 g L-1. The addition of element salts affected the callus content of khellin and vinsangen compounds.